Nile BDC hard seat - Science in the Challenge Program on Water and Food (and CPWF in the new CGIAR) - Harrington, Larry W. (International Livestock Research Institute, 2011)
In this 'hard seat' interview on 5 May 2011, Shirley Tarawali (ILRI) interviewed Larry Harrington (CPWF) about research and science in the Challenge Program on Water and Food (and the CPWF future in the new CGIAR) - http://www.waterandfood.org. The interview was part of the Nile Basin Development Challenge (http://nilebdc.org) 'science and reflection' workshop in Addis Ababa in May 2011.